From Curiosity to Understanding: Implementing the Know-Want-Learn Strategy in Eleventh Grade at SMA Negeri 2 Kota Kupang - Gracia M. N Otta; Elisabeth Pereira Padatu; Dewi I. N. Bili Bora; Elisna Huan (International Journal of Studies in International Education, 2024)
This study explores the implementation of the Know-Want-Learn (K-W-L) strategy to enhance reading comprehension among eleventh-grade students at SMA Negeri 2 Kota Kupang during the 2023/2024 academic year. Employing a Classroom Action Research (CAR) methodology, the research aims to determine the extent to which the K-W-L approach improves students' reading comprehension abilities. The study was conducted in two cycles, each involving planning, action, observation, and reflection phases. Data were collected through pre-tests and post-tests, observation checklists, and student interviews. Findings indicate a significant improvement in students' reading comprehension, as evidenced by increased test scores and positive feedback during interviews. The K-W-L strategy not only engaged students by sparking their curiosity but also guided them through a structured learning process that enhanced their understanding and retention of reading materials. These results suggest that the K-W-L strategy is an effective pedagogical tool for improving reading comprehension in high school students.